Pemberdayaan Ibu-Ibu PKK Melalui Pelatihan Produksi Keranjang Salak - Anisa Dwi Makrufi; Novia Fetri Aliza (Universitas Muhammadiyah Yogyakarta, 2018)
Kronggahan Hamlet Village Polengan District Srumbung Magelang is one of the producers of salak pondoh. How- ever, the problem in mobilizing the economic potential in the local village is the limited number of basket craftsmen to pack the salak harvest. The purpose of this activity is the guidance and assistance of basket making of salak among PKK Mothers with target area of Kronggahan Hamlet. Methods of this activity include 1) conducting FGDs with local officials; 2) conducting counseling and short demonstration of bamboo shoot baskets; 3) training and mentoring; 4) equipment facilitation; and 5) monitoring and evaluation. The result of the activity is to provide knowledge and training of basket making; informing local officials that people in Srumbung, especially Kronggahan Hamlet need a tool or machine irat (bamboo). Problems in the implementation of basket making activities such as mentoring time is too short; the aid of tools is still limited to manual machines; and the community has not understood the making of baskets until the finishing level. Therefore, the local government needs to prioritize the bottom-up principle of all kinds of assistance as well as programs and continuous mentoring related to the making of baskets massively and intensively to the community. Keywords: PKK group, basket of salak.